2005
DOI: 10.1038/sj.cr.7290332
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping and marker-assisted selection (MAS) of a low glutelin content gene in rice

Abstract: Rice with low glutelin content is suitable as functional food for patients affected with diabetes and kidney failure. The fine mapping of the gene(s) responsible for low glutelin content will provide information regarding the distribution of glutelin related genes in rice genome and will generate markers for the selection of low glutelin rice varieties. Following an SDS-PAGE screen of rice germplasm from Taihu Valley of China, Japonica selection W3660 is identified to be a novel mutant characterized with low g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…This suggests that they are closely linked to the mite resistant genes. Similar findings were also observed by Wang et al (2005). They reported that the selection efficiencies of SSR2-004 and RM1358 were 96.8% and 92.7%, respectively, and 99.8% in combination.…”
Section: Discussionsupporting
confidence: 76%
“…This suggests that they are closely linked to the mite resistant genes. Similar findings were also observed by Wang et al (2005). They reported that the selection efficiencies of SSR2-004 and RM1358 were 96.8% and 92.7%, respectively, and 99.8% in combination.…”
Section: Discussionsupporting
confidence: 76%
“…Rice breeders across the globe have worked to increase the protein content of some cultivars and decrease the levels in others (Wang et al 2005. Low protein is desired for those that must curtail their protein intake, such as those with renal disease and for use in sake production to reduce off-flavor creation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in the past decade, the inheritance of many agricultural traits, resistance to pests/disease, stress tolerance, and quality of crops have been widely studied using molecular markers (e.g., RFLP, SSR, RAPD, and AFLP), consequently providing molecular markers for MAS as well. On the basis of genetic information, several successful examples of MAS combined with phenotype measurement have been accomplished, and these mainly focus on the improvement of discontinuous traits such as resistance to pests/disease, stress tolerance, and grain quality in crops (Davierwala et al 2001;Huang et al 2003;Zhou et al 2003;Chen et al 2004;He et al 2004;Joseph et al 2004;Sharma et al 2004;Yi et al 2004;Tan et al 2005;Wang et al 2005;Liu et al 2006;Miyata et al 2007). However, there have been only a few reports on quantitative trait improvements by MAS in rice thus far, especially on the yield-related traits, although a larger number of QTLs associated with yield and yield components have been identified in rice.…”
Section: Discussionmentioning
confidence: 98%
“…Further, the property of relatively small effects of an individual QTL possibly leads to the failure of QTL-MAS (Ashikari and Matsuoka 2006). Therefore, up to date, there are only a few reports on successfully developing a rice cultivar with an improved yield level by MAS, although improvements on resistance to pests/ disease, grain quality, and stress tolerance traits, which are controlled by major genes, have been successfully achieved (Davierwala et al 2001;Huang et al 2003;Zhou et al 2003;Chen et al 2004;He et al 2004;Joseph et al 2004;Sharma et al 2004;Yi et al 2004;Tan et al 2005;Wang et al 2005;Liu et al 2006;Miyata et al 2007;Neeraja et al 2007).…”
mentioning
confidence: 97%